Epidemiology of lumbar disc herniations in adults with low back pain in Enugu, Nigeria - Anyanwu, Godson E.; Ekwunife, Remigius T.; Iyidobi, Emmanuel C.; Nwadinigwe, Cajetan U.; Ekwedigwe, Henry C.; Agu, Augustine U.; Agbo, Emmanuel O. (International Journal of Research in Orthopaedics, 2019)
Background: Lumbar intervertebral disc herniation is used to describe a spectrum of anatomical abnormalities involving disc extension beyond the interspace. It follows a tear in the annulus fibrosus of the intervertebral disc. It is one of the most common causes of low back pain among adults. The study aims to assess the epidemiological pattern of lumbar disc herniations among adults with low back pain in Enugu urban. Methods: The study was a prospective study at National Orthopedic Hospital Enugu and Annunciation Specialist Hospital Enugu. Following ethical approval and written informed consent, patients who met the inclusion criteria were consecutively recruited. The MRI scans of the participants were viewed using DICOM® (Digital Imaging and Communications in Medicine) software on laptop computer. The data included the patients’ demographics, functional disability index for back pain, weight, height, the anatomical level(s) and site(s) of the herniated disc among other parameters. Results: A total of 81 subjects who met the inclusion criteria were included and analyzed using SPSS version 20.0. The mean age of the subjects is 52.99±13.13 years. The most common affected age group is 51-60 years (27.2%). Majority of the subjects (68; 84%) had multiple level herniations which usually includes L4 level(74; 91.4%). Conclusions: That multilevel lumbar disc herniation is far more common than single level herniation with a prevalence of 84% among adults with low back pain in Enugu urban. That, there is statistically significant association of lumbar disc herniation and increasing age.